Michael Vey : Hunt for Jade Dragon / 4. - Evans, Richard Paul (Michael Vey, 2014)
Michael, Taylor, Ostin, and the rest of the Electroclan head to Taiwan in search of nine-year-old child prodigy Lin Julung, or Jade Dragon, who the Elgen kidnapped for Hatch's army of electric children.